Effects of different measurements of foot angle on vital activities of hemodialysis patients (Annals of Medical Research, 2023)
Aim: Individuals who receive hemodialysis treatment due to chronic renal failure have limitations in their daily lives and a decrease in physical activity and walking speed. In this study, we have investigated the effectiveness of various measurements of ankle angles of hemodialysis performed on patients on balance, falling risk, and daily life activities.Materials and Methods: 114 volunteer hemodialysis patients with a mean age of 30-94 have measured at the position of plantar flexion, inversion, and eversion by a 1-degree sensitivity manual goniometer. The Time Up and Go test (TUG), Lawton and Brody Instrumental Activities of Daily Living (IADL) Scale and Barthel Index (BI) were applied to the patients. Statistical analyses were made with the SPSS 25 program.Results: 55 male and 59 female participants were accompanied in the study. The average age was 62.8 ± 15.29, the average hemodialysis duration was 5.59 ± 3.92, the average body mass index was 5.08 ± 5.1 and he average number of falls was 5.59 ± 3.92. A low positive significant correlation was observed between plantar flexion and inversion foot angle measurements with The Lawton and Brody IADL scale (p
Keywords: Hemodialysis; Chronic renal failure; Falling risk; Balance; Food angle measurement